2005
DOI: 10.1021/ma050786r
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible Behavior of Associating Polymer Solutions:  Thermothinning versus Thermothickening

Abstract: Self-assembling properties of poly(sodium acrylate) grafted with dodecyl [C12], PAAgC12, or poly(N-isopropylacrylamide) [PNIPA] side chains, PAAgPNIPA, were studied in unentangled semidilute aqueous solution. While PAAgC12 self-associates through hydrophobic interactions, the gelation of PAAgPNIPA is triggered by heating in response to the lower critical solution temperature of PNIPA (LCST ∼ 32 °C). The local structure of the physical networks was investigated by small-angle neutron scattering, and the scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…This association is strong at low temperature as the enthalpy associated to the extraction of a dodecyl group from a hydrophobic domain is positive. [31] The hydrophobic microdomains constitute the crosslinking points of the reversible network ( Figure 9b). As was mentioned in the previous work of hydrophobically modified PNIPAM [56] , a non-negligible proportion of the NIPAM units neighboring the hydrophobic microdomains should be dehydrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This association is strong at low temperature as the enthalpy associated to the extraction of a dodecyl group from a hydrophobic domain is positive. [31] The hydrophobic microdomains constitute the crosslinking points of the reversible network ( Figure 9b). As was mentioned in the previous work of hydrophobically modified PNIPAM [56] , a non-negligible proportion of the NIPAM units neighboring the hydrophobic microdomains should be dehydrated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rheological properties of hydrophobically modified water-soluble polymers such as polyacrylamide [26][27][28] , poly(dimethylacrylamide) [29] , and poly(sodium acrylate) [29][30][31] have attracted an increasing interest in the last decade. Beyond a threshold concentration, the viscosity increases rapidly with the concentration, due to the formation of interchain aggregates between the hydrophobic groups; these aggregates act as crosslinks leading to reversible physical network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the polyelectrolyte nature of the backbone, polymers with higher contents of hydrophobic groups remain soluble. Hourdet et al [112] have studied PAA grafted with dodecyl chains and found a strong increase of the viscosity with increasing concentration. The temperature dependence of the terminal relaxation time could be characterized by an activation energy of 150 kJ/mol, which differs from that of HEUR containing the same alkyl groups (Ea = 42 kJ/mol).…”
Section: Polymers With Many Associative Groupsmentioning
confidence: 99%
“…Thermothickening polymers have attracted much attention as a result of their special behaviors and several aqueous systems which display such thermoassociative properties have been developed in the last four decades. All these aqueous systems can be classified into three different groups: aqueous solutions of cellulosic derivatives (6-9), block copolymers (10)(11)(12)(13)(14) and graft copolymers (15)(16)(17)(18)(19)(20). Although all the systems exhibit a thermothickening behavior, only the graft copolymers, which were developed by Hourdet at the beginning of the 1990s, really provide a systematic way to explore the key relations existing between the main structure of the copolymer and its flow properties with the temperature.…”
Section: Introductionmentioning
confidence: 99%